Signs of Verbal Resistance in the Brave Pink and Hero Green Campaign Posters - Salsabila, Sherli; Permanaludin, Udayani; Sakinah, R.Myrna Nur (Journal of English Language and Education, 2026)
Language in political campaign posters is increasingly significant as a medium for expressing public resistance and shaping socio-political meaning. This research explores verbal signs in the Brave Pink and Hero Green campaign posters that emerge from the large-scale Indonesian demonstrations in August 2025. During this period, public support for the movement widely appears on social media, not only through the replacement of profile pictures with Brave Pink and Hero Green template, but also through the creation of digital resistance posters. These posters function as a medium for expressing opposition and solidarity through textual elements. Focusing on captions, slogans, and short verbal expressions, this research applies a qualitative descriptive approach. The analysis begins with a descriptive examination of textual elements and proceeds with their classification into Charles Sanders Peirce’s semiotic categories of icon, index, and symbol. The findings indicate that verbal signs play a central role in constructing meanings of resistance within digital campaign media.